Rice calcium/calmodulin-dependent protein kinase directly phosphorylates a mitogen-activated protein kinase kinase to regulate abscisic acid responses. Issue 5 (25th February 2021) - Chen, Min; Ni, Lan; Chen, Jing; Sun, Manman; Qin, Caihua; Zhang, Gang; Zhang, Aying; Jiang, Mingyi
Abstract: Calcium (Ca 2+ )/calmodulin (CaM)-dependent protein kinase (CCaMK) is an important positive regulator of abscisic acid (ABA) and abiotic stress signaling in plants and is believed to act upstream of mitogen-activated protein kinase (MAPK) in ABA signaling. However, it is unclear how CCaMK activates MAPK in ABA signaling. Here, we show that OsDMI3, a rice ( Oryza sativa ) CCaMK, directly interacts with and phosphorylates OsMKK1, a MAPK kinase (MKK) in rice, in vitro and in vivo. OsDMI3 was found to directly phosphorylate Thr-25 in the N-terminus of OsMKK1, and this Thr-25 phosphorylation is OsDMI3-specific in ABA signaling. The activation of OsMKK1 and its downstream kinase OsMPK1 is dependent on Thr-25 phosphorylation of OsMKK1 in ABA signaling. Moreover, ABA treatment induces phosphorylation in the activation loop of OsMKK1, and the two phosphorylations, in the N-terminus and in the activation loop, are independent. Further analyses revealed that OsDMI3-mediated phosphorylation of OsMKK1 positively regulates ABA responses in seed germination, root growth, and tolerance to both water stress and oxidative stress. Our results indicate that OsMKK1 is a direct target of OsDMI3, and OsDMI3-mediated phosphorylation of OsMKK1 plays an important role in activating the MAPK cascade and ABA signaling. Abstract : In rice, the calcium/calmodulin-dependent protein kinase directly phosphorylates and activates a mitogen-activated protein kinase, which plays an important role in abscisic acid signaling.